1975
DOI: 10.2307/2786230
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Formation: An Integrative Model

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
(38 reference statements)
4
12
0
Order By: Relevance
“…Most social psychological theories of coalition formation attempt to account for the occurrence of coalitions according to the resources that individuals control (for some exceptions see Lawler & Youngs, 1975;Mazur, 1968;Taylor, 1970). One of the reasons for the supposed importance of resources is that they affect the proportion of the payoff an individual expects to obtain, or is able to obtain, in various coalitions (Gamson, 1961b;Komorita & Chertkoff, 1973).…”
Section: Relationship Of Present Research To Previous Coalition Researchmentioning
confidence: 99%
“…Most social psychological theories of coalition formation attempt to account for the occurrence of coalitions according to the resources that individuals control (for some exceptions see Lawler & Youngs, 1975;Mazur, 1968;Taylor, 1970). One of the reasons for the supposed importance of resources is that they affect the proportion of the payoff an individual expects to obtain, or is able to obtain, in various coalitions (Gamson, 1961b;Komorita & Chertkoff, 1973).…”
Section: Relationship Of Present Research To Previous Coalition Researchmentioning
confidence: 99%
“…These efforts notwithstanding, it was not until Vinacke and Arkoff (1957) simplified the theory even further that the theory was adopted in social psychology (Chertkoff, 1970;Tedeschi, Schlenker, & Bonoma, 1973), and political science (Riker, 1962). Such adoptions have generally been directed towards reformulating the logic imposed by game theory, and also relaxing its assumptions in an attempt to increase its applicability (Komorita, 1979;Lawler & Youngs, 1975;Miller, 1979). However, the basic constraints imposed by game theory have severely restricted the applicability of these attempts at predicting coalition formation in an organizational setting.…”
Section: Conflict In Organizational Buyingmentioning
confidence: 97%
“…These needs focus on the attitudes individuals have towards the aims and internal environment of a coalition and their need to behave in a manner consistent with those attitudes. Research by Lawler and Youngs (1975) has shown that ideological factors play an important role in coalition formation. Since a person's behavior is dependent on what that person wants to do, and since joining or forming a coalition involves adhering to group norms, ideological needs assume importance in coalition formation in the BC.…”
Section: Individual Needs Of Bc Membersmentioning
confidence: 98%
See 1 more Smart Citation
“…Lawler and Youngs ( 1975) did a questionnaire study which indicates that attitudinal differences among parties have a stronger influence on coalition behavior than several other variables, including power differences. Leiserson's ( 1970) own experimental study confirms the predictions of the minimal distance theory.…”
Section: Attitudinal Similarity Control and Coalition Formationmentioning
confidence: 99%